Precision local positioning mechanism in underground mining using IoT-enabled WiFi platform. Issue 3 (2nd April 2020) - Mohapatra, Ambarish G.; Keswani, Bright; Nanda, Shivani; Ray, Abhishek; Khanna, Ashish; Gupta, Deepak; Keswani, Poonam
ABSTRACT: Internet of Things (IoT) connects many physical devices to many individuals from earth to space. This new concept covers almost all applications such as smart cities, industries, autonomous systems, and underground setups. This article summarizes the application of IoT-driven wireless nodes and IoT decision support platform in underground mining areas where location estimation of the miners is a critical task for the mining administrators. The underground mining accident is one of the most critical environmental disasters where life risk of the miners is a very crucial factor to be addressed. There are very few research work reported to find real-time location of the miner without any Global Positioning System (GPS) and mobile signals. This work demonstrates an efficient local positioning mechanism where low-cost and high battery capacity WiFi nodes are used to find the location of the miner during crude environmental conditions. The whole local positioning system works on the basis of Receiver Signal Strength Indicator (RSSI) value of the miner nodes. This article also demonstrates the useful technique to increase the battery life more than one year. Apart from all the above technological uses, it has been proposed that the localization algorithm can be used as potential technological key for local positioning in underground mines.